Inhibitory Effects of Caulerpa racemosa, Ulva intestinalis, and Lobophora challengeriae on Tyrosinase Activity and α-MSH-Induced Melanogenesis in B16F10 Melanoma Cells - Pradtana Choosuwan; Jantana Praiboon; Korawinwich Boonpisuttinant; Anirut Klomjit; Narongrit Muangmai; Rapeeporn Ruangchuay; Anong Chirapart (Life, 2023)
Melanogenesis involves a synthesis of melanin pigment and is regulated by tyrosinase. The addition of whitening agents with tyrosinase-inhibiting properties in cosmetics is becoming increasingly important. In this study, the ethanolic extracts from twelve seaweeds were assessed for tyrosinase-inhibiting activity using mushroom tyrosinase and melanin synthesis in B16F10 melanoma cells. The highest mushroom tyrosinase inhibition (IC50) was observed with Lobophora challengeriae (0.15 ± 0.01 mg mL−1); treatment was more effective than kojic acid (IC50 = 0.35 ± 0.05 mg mL−1), a well-known tyrosinase inhibitor. Three seaweeds, Caulerpa racemosa, Ulva intestinalis, and L. challengeriae, were further investigated for their ability to reduce melanogenesis in B16F10 cells. The ethanolic extracts of C. racemosa, U. intestinalis, and L. challengeriae showed inhibitory effects by reducing melanin and intracellular tyrosinase levels in B16F10 cells treated with α-melanocyte stimulating hormone in a dose-dependent manner. C. racemosa (33.71%) and L. challengeriae (36.14%) at 25 µg mL−1 reduced melanin production comparable to that of kojic acid (36.18%). L. challengeriae showed a stronger inhibition of intracellular tyrosinase (decreased from 165.23% to 46.30%) than kojic acid (to 72.50%). Thus, ethanolic extracts from C. racemosa, U. intestinalis, and L. challengeriae can be good sources of natural tyrosinase inhibitors and therapeutic or cosmetic agents in the future.